PENGARUH KEPEMILIKAN INSTITUSIONAL, KARAKTER EKSEKUTIF DAN KONEKSI POLITIK TERHADAP TAX AVOIDANCE - Laras Maulina; Syamsul Mu’arif (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
This research aims to determine the influence of Institutional Ownership, Executive Characteristics, and Political Connections on Tax Avoidance. This study employs a quantitative research type, using secondary data. The research data sources were obtained from companies in the energy sector listed on the Indonesia Stock Exchange (IDX) over a five-year period between 2018 and 2022. The sampling method used in this research is purposive sampling, resulting in a sample of 11 companies obtained using this method. The data analysis technique used is panel data regression using E-views 12. The results of this research partially indicate that Institutional Ownership has a positive effect on Tax Avoidance, and Political Connections have a negative effect on Tax Avoidance. Meanwhile, the Executive Characteristics variable has no effect on tax avoidance. Simultaneously, Institutional Ownership, Executive Characteristics, and Political Connections have an effect on Tax Avoidance.